Can Leader–Member Exchange Contribute to Safety Performance in An Italian Warehouse? - Mariani, Marco G.; Curcuruto, Matteo; Matic, Mirna; Sciacovelli, Paolo; Toderi, Stefano (Frontiers in Psychology, 2017)
Introduction: the research considers safety climate in a warehouse and wants to analyze the Leader-Member Exchange role in respect to safety performance. Griffin and Neal’s safety model was adopted and Leader-Member Exchange was inserted as moderator in the relationships between safety climate and proximal antecedents (motivation and knowledge) of safety performance constructs (compliance and participation). Method: survey data were collected from a sample of 133 full-time employees in an Italian warehouse. The statistical framework of Hayes (2013) was adopted for moderated mediation analysis. Results: proximal antecedents partially mediated the relationship between Safety climate and safety participation, but not safety compliance. Moreover, the results from the moderation analysis showed that the Leader-Member Exchange moderated the influence of safety climate on proximal antecedents and the mediation exist only at the higher level of LMX. Conclusions: The study shows that the different aspects of leadership processes interact in explaining individual proficiency in safety practices. Practical implications: Organizations as warehouses should improve the quality of the relationship between a leader and a subordinate based upon the dimensions of respect, trust, and obligation for high level of safety performance.